Marketing Social Innovation Products with IMC - Dwinanto Kurniawan; Nafiah Ariani (Syntax Literate, 2022)
ABSTRACTCumin tea is an herbal product with myriad of benefits. This tea is produced in Tinumpuk Village, Indramayu Regency. Community-based organization that produces this tea belongs to the Ikatan Mantan Buruh Migran–Desa Tinumpuk (IBU TIN). This study aims to determine the application of integrated marketing communication by CBO IBU TIN, especially in marketing cumin tea. This research uses qualitative approach and case study method. The techniques used to collect data are observation, in-depth interviews, and documentation studies. Data analysis technique used Miles & Huberman interactive analysis, while triangulation of data sources was used to test the validity of the data. The results of the study shows that marketing of cumin tea products by CBO IBU TIN has used several elements in integrated marketing communication, namely advertising, sales promotion, personal selling, public relations, event marketing, and packaging. This finding also shows that CBO IBU TIN does not use digital (interactive) communication in marketing the cumin tea products. Keywords: Integrated Marketing Communication, Migrant Workers, Cumin Tea ABSTRAKTeh jinten adalah produk herbal dengan segudang manfaat. Teh ini diproduksi di Desa Tinumpuk, Kabupaten Indramayu. Kelompok berbasis komunitas yang memproduksi teh ini tergabung dalam Ikatan Mantan Buruh Migran–Desa Tinumpuk (IBU TIN). Studi ini bertujuan untuk mengetahui penerapan integrated marketing communication oleh CBO IBU TIN terutama dalam memasarkan teh jinten. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Teknik yang digunakan untuk mengumpulkan data penelitian ialah observasi, wawancara mendalam, dan studi dokumentasi. Teknik analisis data menggunakan analisis interaktif Miles & Huberman, sementara triangulasi sumber data digunakan untuk menguji keabsahan data. Hasil penelitian menunjukkan CBO IBU TIN dalam memasarkan produk teh jinten sudah menggunakan beberapa eleman dalam integrated marketing communication, yaitu advertising, sales promotion, personal selling, public relations, event marketing, dan packaging. Temuan ini juga menunjukkan tidak dimanfaatkannya elemen digital (interactive) communication oleh CBO IBU TIN dalam memasarkan produknya. Kata Kunci: Komunikasi Pemasaran Terpadu, Buruh Migran, Teh Jinten